Pengaruh Model Pendampingan dan Kartu Kendali Faktor Risiko Luka Kaki Diabetik Terhadap Praktik Perawatan Kaki - Wahyu Widagdo (Syntax Corporation Indonesia, 2021)
Diabetes mellitus can affect all organs of the body and cause various kinds of complaints with very varied symptoms. The purpose of the study was to analyze the effect of family assistance models & diabetic foot risk factor control cards on foot care practices in type 2 diabetes mellitus clients. The time of the research will take place in July to October 2019 The population in this study people who suffer from DM in the Pasar Minggu sub-district area with a large sample in accordance with the formula for calculating the number of samples and sampling techniques with purposive sampling technique. The results of the study showed a significant association of assistance with diabetic foot care practices p = 0.003 and a significant relationship between diabetic foot risk factor control cards with DM foot care practices p = 0.000. An increase in the mean value of the mean pre and posttest DM foot care practice in the intervention group and the control group. T test results, the mean posttest of the intervention group was higher than the control group with a p value = 0,000. Recommendations for assistance with clients who have a high risk of diabetic injury. And the need to be socialized and implemented a risk factor control card for diabetic legs.